Dante e il prosimetro. Dalla 'Vita nova' al 'Convivio' (Quaderni di Gargnano, 2022)
This volume presents the Proceedings of the 19th International Conference on Italian Literature in the "Gennaro Barbarisi" series, which took place over 15-23 October 2020. To mark the septcentenary of Dante Alighieri's death (1321-2021), the Conference was dedicated to the theme of Dante and the Prosimetrum. From the 'Vita nova' to the 'Convivio'. Due to the pandemic, the conference could not be held in the usual setting of Palazzo Feltrinelli in Gargnano del Garda, but was organized remotely on four individual days, in collaboration between the Department of Literary Studies, Philology and Linguistics of the University of Milan and the Department of Italian of the University of Fribourg, Switzerland.Questo volume raccoglie gli Atti del XIX Convegno internazionale di Letteratura italiana "Gennaro Barbarisi", svoltosi a distanza, a causa della pandemia, tra il 15 e il 23 ottobre del 2020 e dedicato, nella ricorrenza del settecentesimo anniversario della morte di Dante Alighieri (1321-2021), a Dante e il prosimetro. Dalla 'Vita nova' al 'Convivio'. Le quattro giornate di studio, che non si sono potute tenere nella consueta cornice di Palazzo Feltrinelli a Gargnano del Garda, sono state organizzate in collaborazione fra le due sedi del Dipartimento di Studi letterari, filologici e linguistici dell'Università degli Studi di Milano e del Dipartimento di Italiano dell'Università di Friburgo in Svizzera.
Keywords: Dante Alighieri; prosimetro; prosimetrum; Vita nova; Convivio; rime; lyric poetry; prosa; prose; letteratura italiana; Italian literature; centenario dantesco; Dante Studies